Struggles to Improve Students' Entrepreneurship Interest Through GEPPRAK Learning Model - Irmawati, Irmawati; Murtini, Wiedy; Hakim, Lukman (Dinamika Pendidikan, 2020)
This study aims to investigate the implementation of "GEPPRAKâ€ learning model to increase the class XII studentsâ€™ interest in entrepreneurship in SMA Negeri 2 Surakarta. The design used in this study is true experimental design using pretest - posttest control group design. The experimental group and the control group were given the pretest. Then the experimental group was given the treatment. After that, a posttest was carried out on the experimental group and the control group. Data was collected by documentation, observation and questionnaire described according to the findings. Data analysis techniques in this study used an independent sample t-test. The results of this study were indicated a significant increase in studentsâ€™ interest in entrepreneurship in the experimental class given treatment using the GEPPRAK learning model. This is evidenced by testing used the t-test and obtained the significance of the average difference test post-test Sig (2-tailed) 0.017 Î± (= 0.05) and t arithmetic (2.426) t table (1.980). Therefore, the decision test H0 rejected means that there are differences in the average scores post-test of students in the experimental class and the control class. The difference in the average scores post-test of students explains that treatment in the experimental class can increase studentsâ€™ entrepreneurial interest.